Artificial Intelligence Integration and the Reconfiguration of Organizational Control Systems A Critical Literature Review of Knowledge Governance Structural Transformation and Strategic Renewal - Fahrezi, Muhammad (International Journal of Research and Applied Technology (INJURATECH), 2025)
The integration of Artificial Intelligence has profoundly challenged the foundations of organizational control systems traditionally based on hierarchical authority, formal rules, and managerial supervision. While existing studies largely emphasize the operational benefits of Artificial Intelligence, limited attention has been given to its implications for control structures, knowledge governance, and strategic renewal. This study aims to critically examine how Artificial Intelligence reconfigures organizational control systems through an integrative literature review. Adopting a critical and interpretive synthesis of interdisciplinary scholarship, this paper explores the transformation of control logic, the mediating role of knowledge governance, and the structural conditions that enable strategic renewal. The findings suggest that Artificial Intelligence shifts organizational control from compliance-oriented supervision toward adaptive, algorithmically mediated coordination embedded in digital infrastructures. This reconfiguration redistributes control authority, reshapes organizational structures, and enables continuous strategic sensemaking. The study contributes by offering a holistic conceptual framework that positions Artificial Intelligence as a catalyst for a new paradigm of organizational control rather than a mere technological enhancement.